2017
DOI: 10.1111/trf.14112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical methods of cryopreservation for donor lymphocyte infusions vary in their ability to preserve functional T‐cell subpopulations

Abstract: This study has important implications in determining the best cryoprotectant solution for specific clinical applications in allogeneic immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…Another study found that the use of 10% DMSO for cryopreservation resulted in lower post-thaw viability for most lymphocyte subpopulations, especially CD3 + CD4 + and Tregs, as well as growth arrest of CD3 + cells in the G2/M phase [63]. These might account for loss of functional cells in cryopreserved T-cell product for immunotherapy.…”
Section: Emerging Approachesmentioning
confidence: 96%
“…Another study found that the use of 10% DMSO for cryopreservation resulted in lower post-thaw viability for most lymphocyte subpopulations, especially CD3 + CD4 + and Tregs, as well as growth arrest of CD3 + cells in the G2/M phase [63]. These might account for loss of functional cells in cryopreserved T-cell product for immunotherapy.…”
Section: Emerging Approachesmentioning
confidence: 96%
“…Why CryoStor CS10 was better than 10% DMSO and 90% FCS is not evident from our experiments; however, several previous studies reported better cell survival fol-lowing cryopreservation in a variety of experimental systems with the use of CryoStor solutions over a number of other cryopreservation media. [9][10][11][12] CryoStor CS10 is a serum-free, protein-free, animal component-free intracellular-like defined cryopreservation medium containing 10% DMSO that has been designed to better maintain the ionic balance of cells at hypothermic and freezing temperatures and allow for more rapid recovery by reducing cryopreservation-induced stress and damage. [9][10][11][12] The design of CryoStor CS10 includes pH buffering, free radical scavenging, oncotic/osmotic support, energy substrates, and ionic concentrations for increased balance at ultralow temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cryostor (BioLife Solutions), a commercially available cryoprotectant, has demonstrated comparable cell viability and postthaw recovery similar to our home‐brewed cocktail. A validation process is under way for its use in multi‐institutional trials as a standardized method . Cryopreserved products are stored in vials (Nunc Cryotube Vials, Roskilde) or in polyfluoroethylene bags (KryoSure, American Fluoroseal Corporation).…”
Section: Cryopreservationmentioning
confidence: 99%